2021
DOI: 10.3400/avd.oa.20-00132
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Investigating the Use of Regional Oxygen Saturation as a Predictor of Ischemic Wound Healing Outcome after Endovascular Treatment in Patients with Chronic Limb-Threatening Ischemia

Abstract: Objective: To determine the prognostic value of regional tissue oxygenation saturation (rSO 2) for ulcer healing after endovascular treatment (EVT) of peripheral arterial disease (PAD). Materials and Methods: Among PAD patients, 34 patients with chronic limb-threatening ischemia underwent EVT for limb salvage. We retrospectively analyzed the cutoff rSO 2 values on postoperative day 1 to predict ulcer healing and patient prognosis. Skin perfusion pressure (SPP) and transcutaneous oxygen pressure (TcPO 2) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
8
0
5
Order By: Relevance
“…A previous study identified that an rSO 2 of more than 50% may be a cut-off value for wound healing. 28 ) Patient cardiac function, physique, and skin color do not influence the rSO 2 value. Therefore, TOE-20 may become an ideal diagnostic device to monitor tissue perfusion/oxygenation in real-time.…”
Section: Discussionmentioning
confidence: 91%
“…A previous study identified that an rSO 2 of more than 50% may be a cut-off value for wound healing. 28 ) Patient cardiac function, physique, and skin color do not influence the rSO 2 value. Therefore, TOE-20 may become an ideal diagnostic device to monitor tissue perfusion/oxygenation in real-time.…”
Section: Discussionmentioning
confidence: 91%
“…All patients with an rSO 2 of ≥50% in the dorsal foot on postoperative day 1 exhibited improved ulcer healing, indicating that an rSO 2 of ≥50% might be a cutoff value for wound healing. 8 Further studies with longer observation periods are required to verify the cutoff value of rSO 2 for wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…A finger-worn tissue oximeter that uses NIRS technology has been developed (Toccare: Astem Co., Ltd., Kawasaki, Japan) to measure rSO 2 values to depths of 0–5 mm below the skin surface. According to several research reports, NIRS enables a painless and simple measurement of rSO 2 in any area of the foot and reflects microcirculation [ 37 , 38 , 39 ]. While these advantages are similar to those of SMI, NIRS is difficult to quantify; SMI is superior to NIRS for the quantitative assessment of foot microcirculation.…”
Section: Discussionmentioning
confidence: 99%